(untitled) (Revista Electrónica Calidad en la Educación Superior, 2022)
The current economic situation has facilitated the structuring of this project whose approach is aimed at generating creative ideas from the classroom in which each student cultivates their entrepreneurial spirit and broadens their vision to offer an innovative solution to an existing problem of this nature, with the objective of developing creative proposals, supported by learning strategies with the use of ICTs as the resources that most facilitated the understanding of content and communication among the students of the Analogue and Digital Reproduction subjects of the Visual Arts and Design career in Press of the Plastic Arts and Design career, where the support and cooperative work merged creativity in obtaining various design prototypes for commercial products aimed at solving the needs of a society that evolves every day. In conclusion, this project allowed students to analyze strategies and new possibilities to work on a common project, which supported the development of their skills by applying what they learned in virtual classes with a view to future endeavors.